2009
DOI: 10.2135/cropsci2008.12.0689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Divergence on the Ratio of Variance Due to Specific vs. General Combining Ability in Winter Triticale

Abstract: The objective of our study was to examine the influence of genetic divergence on the ratio of the components of variance for specific (σ2SCA) and general (σ2GCA) combining ability using experimental data in triticale (×Triticosecale Wittm.). In total, 21 lines and their 210 crosses were evaluated for grain yield in field trials. Published molecular data were reanalyzed, indicating an optimum of two subgroups. The estimates of σ2SCA and σ2GCA were determined for the total diallel and between the two subgroups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Based on quantitative genetic theory, it has been shown that genetically distinct heterotic groups decrease the 2 2 SCA GCA / s s ratio, supporting GCA-based hybrid prediction (Reif et al, 2007). These findings were confirmed in experimental studies by, for instance, Fischer et al (2009) using 210 single-cross triticale hybrids. The two-way hybrids in our study are based on genetically distinct male and female pools (Fig.…”
Section: High Prediction Ability Of Hybrid Performance Based On Gca Ementioning
confidence: 67%
“…Based on quantitative genetic theory, it has been shown that genetically distinct heterotic groups decrease the 2 2 SCA GCA / s s ratio, supporting GCA-based hybrid prediction (Reif et al, 2007). These findings were confirmed in experimental studies by, for instance, Fischer et al (2009) using 210 single-cross triticale hybrids. The two-way hybrids in our study are based on genetically distinct male and female pools (Fig.…”
Section: High Prediction Ability Of Hybrid Performance Based On Gca Ementioning
confidence: 67%
“…This can be interpreted as an indicator that σ 2 GCA is of low importance and consequently, this suggests that prediction accuracy can only be enhanced slightly by considering GCA eff ects. Increasing genetic divergence of the two parental populations tends to lead to a high ratio of σ 2 GCA vs. σ 2 SCA (Fischer et al, 2009). This is supported by a significant association between mid-parent and hybrid performance and therefore, relevance of additive gene actions.…”
Section: Prediction Of Hybrid Performancementioning
confidence: 82%
“…The σ 2 GCA /σ 2 SCA ratio in hybrids varies depending on the allele frequencies between parents (Reif et al, 2007). Increasing genetic divergence of the two parental populations tends to lead to a high ratio of σ 2 GCA vs. σ 2 SCA (Fischer et al, 2009). Therefore, development of genetically divergent heterotic groups is pivotal for establishing a hybrid breeding program in durum wheat.…”
Section: Prediction Of Hybrid Performancementioning
confidence: 99%
“…The last example is a dataset of triticale (×Triticosecale Wittm.) (Fischer et al, 2009). The experiment was replicated twice in each of fi ve locations and included 280 entries in an α-design with 28 blocks and 10 entries per block.…”
Section: Datasetsmentioning
confidence: 99%
“…Given this approach, fitting of a mixed model to complex block structures, spatial error structures and heterogeneous variances within the mixed‐model approach is straightforward. Later in this paper, we will demonstrate the implementation with three datasets described in the literature (Hayman, 1954; Lonnquist and Gardner, 1961; Fischer et al, 2009).…”
mentioning
confidence: 99%